Employment Experience of Remote Workers - Apelo, Ena Louise P. (Technium Social Sciences Journal, 2026)
This study examined the employment experience of remote workers through a phenomenological approach. Data were collected through semi-structured interviews with ten participants aged 23–50; with at least one year of remote work experience and had workloads equivalent to full-time employment, working for clients based outside the Philippines. A thematic analysis following Creswell’s approach revealed five major themes: (1) A Leap of Faith Into an Unfamiliar Landscape, (2) A Self-Defined, Blended, Multi-Role Identity, (3) A Non-Traditional and Multicultural Remote Work Ecosystem, (4) Unique Benefits, Burdens, and Adaptations in Remote Work, and (5) Future Directions and the Evolving World of Remote Work. The themes explored how many participants began their remote careers through invitations or risk-taking, viewing remote work as an uncertain yet promising alternative to traditional career paths. Over time, they developed flexible, multi-role professional identities shaped by continuous learning and experiences. Their work experiences were influenced by organizational structures, company culture, and professional relationships. While remote work offered benefits of comfort, autonomy, and greater opportunities for family-centered living, it also entailed tradeoffs relating to personal, ethical and systemic challenges. Looking towards the future, many viewed remote work as a platform for growth rather than a permanent destination. The findings suggest that remote work can be meaningfully situated within work psychology frameworks emphasizing motivation, self-efficacy, identity development, job crafting, and well-being. Filipino psychology also provided valuable insight into how cultural values shape remote workers’ attitudes toward relationships, responsibility, and resilience in a global work setting. This study contributes to a deeper understanding of the employment experience of Filipino remote workers and offers implications for support programs, public education, and policy development.